Pneumothorax in patients with idiopathic pulmonary fibrosis: a real-world experience - Yamazaki, Ryo (BMC Pulm Med, 2021)
BACKGROUND: Some patients with idiopathic pulmonary fibrosis (IPF) develop pneumothorax. However, the characteristics of pneumothorax in patients with IPF have not been elucidated. The purpose of this study was to clarify the clinical course, actual management, and treatment outcomes of pneumothorax in patients with IPF. METHODS: Consecutive patients with IPF who were admitted for pneumothorax between January 2008 and December 2018 were included. The success rates of treatment for pneumothorax, hospital mortality, and recurrence rate after discharge were examined. RESULTS: During the study period, 36 patients with IPF were admitted with pneumothorax a total of 58 times. During the first admission, 15 patients (41.7%) did not receive chest tube drainage, but 21 (58.3%) did. Of the 21 patients, 8 (38.1%) received additional therapy after chest drainage. The respective treatment success rates were 86.6% and 66.7% in patients who underwent observation only vs chest tube drainage. The respective hospital mortality rates were 13.3% and 38.0%. The total pneumothorax recurrence rate after hospital discharge was 34.6% (n = 9). CONCLUSIONS: Pneumothorax in patients with IPF was difficult to treat successfully, had a relatively poor prognosis, and showed a high recurrence rate.